Pengaruh Modal Sosial, Dukungan Pemerintah Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja UMKM Kemasan Di Kecamatan Padang Barat Kota Padang - Inda, Inda; Eka Mariyanti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the influence of Social Capital, Government Support, and Human Resource Competence on the performance of SMEs in Padang City. The method used is quantitative with a survey approach, where data was collected from 82 SME actors in the packaging sector in West Padang District. Sampling was carried out using purposive sampling, and data was collected through questionnaires distributed to 84 respondents. The collected data was then analyzed using SPSS Version 26. The results show that Social Capital, Government Support, and Human Resource Competence each have a significant influence on SME performance. Simultaneously, all three variables also have a significant effect on the performance of SMEs in Padang City.